PENCIPTAAN MOTIF BATIK SUMBER IDE DARI ORNAMEN MASJID DAN MAKAM MANTINGAN - Ismia, Ufik Nur; Na’am, Muh Fakhrihun; Nazwan, Atikah Putri (Fashion and Fashion Education Journal, 2021)
CREATION OF BATIK MOTIF FROM THE MANTINGAN MOSQUE AND TOMB ORNAMENTS Ufik Nur Ismia *)a, Muh Fakhrihun Na’am *)b Department of Family Welfare Education, Faculty of Engineering State University of Semarang, E7 Campus Sekaran Gunungpati Semarang Building 50229 Email: ufikjepara123@gmail.com Abstract: Batik motifs are one of the most important factors in realizing a work of batik, by taking the source of ideas such as: abstract motifs, flora and fauna motifs, ornaments, decorative carvings, and so forth. With various sources of ideas avaible, researchers are interested in the ornaments in , mosques and Mantingan tombs. Apart from being a historical legacy, batik business people in Jepara Regency have not used batik motifs as a source of ideas from ornaments, most of them still use Jepara carvings. The method used in this research is descriptive qualitative research method. The procedure of conducting research is to create a batik motifs that takes the source of the ideas of some of the ornaments in the mosque and the mantingan tomb, and then translates them into a written batik work. Research results by describing the work, the work produced is feasible and needs to be developed with a variety of attractive colors. Keyword: ornaments, Batik Motifs.